Aportes de las TIC para la creación de portafolios virtuales - Huarcaya Aliaga, Ruth (2015)
This article aims to propose the practicaluse of innovative strategies provided inthe context of Information Technologyand Communication (TIC) to universityclassrooms; as is the creation of the virtualportfolio, using Weebly, to demonstratethe ease of creating new teaching tools totransform our teaching.